Diagnosis, Treatment and Prevention of Age-Related Macular Degeneration - Kodjikian, Laurent (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In this reprint, we hope to review the basics and highlight the latest developments in AMD. This demonstrates the benefits of the international scientific community working on this disease, to limit its negative impacts, the most vital of which is the loss of visual function, leading to a loss of autonomy and a decrease in patients' quality of life.